2021
DOI: 10.3390/jcm11010206
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Prediction of Macrophage Activation Syndrome in Still’s Disease

Abstract: Distinguishing between macrophage activation syndrome (MAS) and a simple flare of Still’s disease (SD) may be challenging. We sought to clarify the clinical features and outcome of MAS in SD and to explore predictive factors of MAS development. Demographic and clinical data, treatments, and outcomes were recorded in a cohort of 206 SD patients. SD patients with and without MAS were compared. To explore predictive factors for the development of MAS, patients were compared at the time of SD diagnosis. Twenty (9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
(70 reference statements)
0
15
0
1
Order By: Relevance
“…Yet, considering our findings, the best recommendation is probably to alert the clinician who has to manage a patient with overlapping symptoms that the main (and almost only) differential diagnosis of AOSD flare is a hematological malignancy complicated by HLH. Javaux et al have published different parameters that are useful for distinguishing HLH and AOSD flare, including lower fibrinogen, leukocyte and platelet counts, but no difference in GF fraction [ 7 ]. Another study showed that interleukin (IL)-18 levels have high accuracy for the differential diagnosis of AOSD and HLH but IL-18 is rarely available routinely [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, considering our findings, the best recommendation is probably to alert the clinician who has to manage a patient with overlapping symptoms that the main (and almost only) differential diagnosis of AOSD flare is a hematological malignancy complicated by HLH. Javaux et al have published different parameters that are useful for distinguishing HLH and AOSD flare, including lower fibrinogen, leukocyte and platelet counts, but no difference in GF fraction [ 7 ]. Another study showed that interleukin (IL)-18 levels have high accuracy for the differential diagnosis of AOSD and HLH but IL-18 is rarely available routinely [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, GF reduction has been observed in other conditions, such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection or hemophagocytic lympho-histiocytosis (HLH) [ 4 , 5 , 6 ]. It is noteworthy that Still’s disease and HLH are closely related, as 5–19.5% of patients have overt HLH [ 7 , 8 , 9 , 10 , 11 ], and 16.7–53% have bone marrow features of hemo-phagocytosis [ 12 , 13 , 14 ]. Some authors have even raised the question of a unique continuum between the two diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are primarily designed for research, most physicians use the Yamaguchi [ 9 ] and Fautrel [ 9 , 14 ] classification criteria for AOSD in practice. These two are the most sensitive and specific diagnostic criteria [ 15 ].…”
Section: Aosd-clinical Picture and Diagnostic Criteriamentioning
confidence: 99%
“…Odynophagia and occasionally pharyngitis are symptoms that accompany fever [ 7 ]. Additionally, increased liver enzymes, lymphadenopathy, hepatosplenomegaly, hyperferritinemia, and white-blood-cell count (WBC) of 10,000/mm 3 , primarily neutrophilic polymorphonuclear (PMNs) cells, are frequently detected and supportive of the diagnosis [ 8 , 9 ]. Myalgia is common, although myositis and polymyositis are rare [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dramatic decrease in the number of figurative elements of the blood, coagulation abnormalities, significant liver cytolysis, and the increase in LDH as well as serum ferritin are important laboratory data for the identification of patients with sJIA-MAS. A concentration above 3500 μg/L has 85% sensitivity and 97% predictability for sJIA-MAS, and extreme hyperferritinemia detected at the time of sJIA diagnosis may be a biomarker to foreshadow sJIA-MAS [ 227 ].…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%